Description of Student Responses Toward Implementation Inquiry Learning Model in Physics Learning - Tanti, Tanti; Kurniawan, Dwi Agus; Sukarni, Weni; Erika, Erika; Hoyi, Roro; Ikhlas, Muhammad (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
The learning model is one of the strategic approaches that must be carried out by the teacher systematically and procedurally in organizing learning activities to achieve optimal learning goals. The learning model is very important in the learning process. This research was conducted at Muaro Jambi 8 Public High School on Grade X IPA 1 students which aimed to determine student responses when given an Inquiry Learning model during the physics learning process. The instrument used was a student questionnaire with a sample of 21 students. This research uses a mixed-method with a sequential explanatory design. Data analysis techniques use descriptive statistics to get the average value, mode, median, minimum, maximum. Based on the results of the study found that the level of student response to the learning model is quite good categorized with a percentage of 47,6%.